Antiplatelet therapy after noncardioembolic stroke: an individual patient data network meta-analysis - Greving, Jacoba P.; Diener, Hans-Christoph; Reitsma, Johannes B.; Bath, Philip M.; Csiba, László; Hacke, Werner; Kappelle, L. Jaap; Koudstaal, Peter J.; Leys, Didier; Mas, Jean-Louis; Sacco, Ralph L.; Algra, Ale (Stroke, 2019)
Background and Purpose: We assessed the efficacy and safety of antiplatelet agents after noncardioembolic stroke or transient ischemic attack and examined how these vary according to patients’ demographic and clinical characteristics. Methods: We did a network meta-analysis (NMA) of data from 6 randomized trials of the effects of commonly prescribed antiplatelet agents in the long-term (≥3 months) secondary prevention of noncardioembolic stroke or transient ischemic attack. Individual patient data from 43 112 patients were pooled and reanalyzed. Main outcomes were serious vascular events (nonfatal stroke, nonfatal myocardial infarction, or vascular death), major bleeding, and net clinical benefit (serious vascular event or major bleeding). Subgroup analyses were done according to age, sex, ethnicity, hypertension, qualifying diagnosis, type of vessel involved (large versus small vessel disease), and time from qualifying event to randomization. Results: Aspirin/dipyridamole combination (RRNMA-adj, 0.83; 95% CI, 0.74–0.94) significantly reduced the risk of vascular events compared with aspirin, as did clopidogrel (RRNMA-adj, 0.88; 95% CI, 0.78–0.98), and aspirin/clopidogrel combination (RRNMA-adj, 0.83; 95% CI, 0.71–0.96). Clopidogrel caused significantly less major bleeding and intracranial hemorrhage than aspirin, aspirin/dipyridamole combination, and aspirin/clopidogrel combination. Aspirin/clopidogrel combination caused significantly more major bleeding than aspirin, aspirin/dipyridamole combination, and clopidogrel. Net clinical benefit was similar for clopidogrel and aspirin/dipyridamole combination (RRNMA-adj, 0.99; 95% CI, 0.93–1.05). Subgroup analyses showed no heterogeneity of treatment effectiveness across prespecified subgroups. The excess risk of major bleeding associated with aspirin/clopidogrel combination compared with clopidogrel alone was higher in patients aged <65 years than it was in patients ≥65 years (RRNMA-adj, 3.9 versus 1.7). Conclusions: Results favor clopidogrel and aspirin/dipyridamole combination for long-term secondary prevention after noncardioembolic stroke or transient ischemic attack, regardless of patient characteristics. Aspirin/clopidogrel combination was associated with a significantly higher risk of major bleeding compared with other antiplatelet regimens.
Gesehen am 22.10.2019